MINERALOGICAL AND ORGANIC GEOCHEMICAL EVALUATION OF SHALE GAS POTENTIALITY IN THE BLUE NILE BASIN, SUDAN - ADAM SHOIEB, MONERA ADAM (2017)
The heterogeneity and complexity of shale gas have become clear as the development of unconventional resources has improved. The Blue Nile Basin, located in the eastern part of the Republic of Sudan, is one of the many Mesozoic rift Basins in Sudan associated with the Central African Rift System (CARS) and has been the major focus for shale gas exploration due to the hydrocarbon found in the basin. But so far no success of discovery has been achieved because the shale gas potentiality of the study area is still unknown. The objective of this study is to evaluate the shale gas potential of the Dinder and Blue Nile Formations within the Blue Nile Basin, based on the mineralogical and organic geochemical assessments. Twenty cutting shale samples from Farasha-1 and Tawakul-1 wells of the Dinder and Blue Nile Formations have been used to assess on the rock mineralogy and the quality of the source rock. Results of X-ray Diffraction (XRD) indicate that the cutting shale samples are mainly comprised of clay minerals such as kaolinite and illite and non-clay minerals such as quartz and pyrite. Other minerals found such as calcite, chlorite, goethite and smectite. Scanning electron microscope with energy dispersive X-ray (SEM-EDX) confirmed the minerals that present in XRD. Knowing that the clay mineral composition of the shale can be useful in drilling, the high abundance of clay minerals suggest that fractures and swelling clays are more difficult to be formed in clay-rich shales compared to silica-rich and carbonate-rich shales. The total organic carbon (TOC) content shows fair to good values of 0.7-1.9 wt. % in the Dinder and Blue Nile Formations at Farasha-1 well and poor to fair values of 0.8-1.2 wt. % in Tawakul-1 well. The Hydrogen Index (HI) values are within the range of 12-182 mg HC/g TOC, suggesting the kerogen as mainly Type III and IV, and their potential to generate gas. The type of kerogen also supported by the pyrolysis gas chromatography (Py-GC) with the pyrolysis HI values which indicate that the samples in the Dinder and Blue Nile Formations are dominated by Type III kerogen that can generate mainly gas.